LIVING THINGS IN PRE-SCHOOL: KNOWLEDGE AND EXPERIENCE (Tabanque. Revista Pedagógica, 2017)
The following end of degree paper, for pre-school, the main objective was to teach and expand the children’s knowledge about the animal kingdom through direct interaction with the use of experiments as the fundamental teaching method. This proposal is conducive to learning by using the methodology for projects. Given the current need to inculcate a proper science education to children, even from three years, the activities shown have been developed with the ultimate aim of boosting in students a scientific way to perceive and understand the environment around them.
Keywords: observation; experimentation; science education; work projects and animals